2023
DOI: 10.1109/access.2023.3239895
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Ageing Performance of Alternative Dielectric Fluids

Abstract: Mineral oil has traditionally been used as a cooling fluid in power transformers, but its low biodegradability and low fire point have motivated the search of alternatives. In this work, six different dielectric fluids have been studied, including four vegetable liquids, from sunflower, rapeseed, soybean, and palm, one synthetic ester and a mineral oil used for comparison. These oils were subjected to an accelerated thermal ageing in glass vessels at 150 • C for four weeks (672 hours) in presence of Kraft insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The chemical reaction between oxygen and the hydrocarbons of any insulating liquid causes deterioration in terms of oxidation and ageing of the liquid which leads to the formation of compounds like acids, sludge, water, and gases as presented in Table 10 with their corresponding effects [182], [183]. Also, the DGA results involving about 1.5 million samples based on IEEE C57.104-2019 standard revealed that the O2/N2 ratio is a prominent parameter that exerts a remarkable influence on the typical gas levels detected irrespective of the insulating liquid volume, rating, and voltage class.…”
Section: Oxygen and Ageingmentioning
confidence: 99%
“…The chemical reaction between oxygen and the hydrocarbons of any insulating liquid causes deterioration in terms of oxidation and ageing of the liquid which leads to the formation of compounds like acids, sludge, water, and gases as presented in Table 10 with their corresponding effects [182], [183]. Also, the DGA results involving about 1.5 million samples based on IEEE C57.104-2019 standard revealed that the O2/N2 ratio is a prominent parameter that exerts a remarkable influence on the typical gas levels detected irrespective of the insulating liquid volume, rating, and voltage class.…”
Section: Oxygen and Ageingmentioning
confidence: 99%
“…Moreover, retrofilling transformers with alternative oils reduces insurance costs, limits fire risk, and may extend the life expectancy of transformers [1,2]. It has been proven in the laboratory [3][4][5][6] that the presence of esters slows down the ageing rate of cellulose due to the higher hygroscopicity of these liquids and the hindrance of glucose chain cleavage by transesterification reactions. As a result of the reduced ageing rate of cellulose in the presence of esters, transformer insulation can safely withstand higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Each manufacturer purposefully adds different additives to their product to improve their behavior with respect to acidity, and sometimes their products are not "pure", since they have a mixture of different fluids. Table 1 includes typical values of the properties of different dielectric liquids [12]. The interest in these liquids since the early years of this century is demonstrated by the fact that in 2013 a review work was published in which the evolution of the different insulating liquids, as well as their blends, was exposed.…”
mentioning
confidence: 99%
“…Each manufacturer purposefully adds different additives to their product to improve their behavior with respect to acidity, and sometimes their products are not "pure", since they have a mixture of different fluids. Table 1 includes typical values of the properties of different dielectric liquids [12]. However, the use of these new dielectric fluids for transformers also has some drawbacks, among which two stand out:…”
mentioning
confidence: 99%
See 1 more Smart Citation